2008
DOI: 10.1074/jbc.m802734200
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of Phycobiliproteins

Abstract: All phycobiliproteins contain a conserved, post-translational modification on asparagine 72 of their ␤-subunits. Methylation of this Asn to produce ␥-N-methylasparagine has been shown to increase energy transfer efficiency within the phycobilisome and to prevent photoinhibition. We report here the biochemical characterization of the product of sll0487, which we have named cpcM, from the cyanobacterium Synechocystis sp. PCC 6803. Recombinant apo-phycocyanin and apo-allophycocyanin subunits were used as the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Only after maturation can phycobiliproteins form spontaneously trimers, which are then integrated into the PBSs by interaction with specific structural proteins, so-called linker polypeptides. These post-translational modifications reactions include the covalent attachment of 1-4 chromophores to each individual apoprotein (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), methylation of an asparagine residue (21)(22)(23), and cleavage of N-terminal methionine residue (5, 24) (see UniProtKB/Swiss-Prot entry Q1XDQ2).…”
mentioning
confidence: 99%
“…Only after maturation can phycobiliproteins form spontaneously trimers, which are then integrated into the PBSs by interaction with specific structural proteins, so-called linker polypeptides. These post-translational modifications reactions include the covalent attachment of 1-4 chromophores to each individual apoprotein (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), methylation of an asparagine residue (21)(22)(23), and cleavage of N-terminal methionine residue (5, 24) (see UniProtKB/Swiss-Prot entry Q1XDQ2).…”
mentioning
confidence: 99%
“…PBPs may comprise more than 60 % of the total soluble cellular protein fraction, which is equivalent to almost 20 % of the total dry weight of cyanobacteria (Soni et al, 2008[ 91 ]). The assembly of PBS is initiated with chromophorylation of PBPs, followed by methylation and oligomerization, and linker protein insertion (Miller et al, 2008[ 63 ]). PBS assembly and architecture are driven to facilitate energy transfer from higher to lower energy state.…”
Section: Introductionmentioning
confidence: 99%
“…This change in conformation increases the photosynthetic efficiency by decreasing the excited state proton transfer reactions and intersystem photoisomerization (Zhao et al, 2000[ 105 ]). Since Asn72 is very close to the surface of the protein, methylation of Asn72 also restricts the approach of surrounding solvents and oxygen to the chromophore i.e., photo-oxidation in presence of very high light intensity (Miller et al, 2008[ 63 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the maturation of PBP, another unique posttranslational modification occurs, the methylation of N-asparagine, which is located at the 72 position (consensus numbering), and no such modification has been found on the homologous position (Swanson and Glazer, 1990;Miller et al, 2008;Shen et al, 2008). Minami et al first reported that ApcB of Anabaena cylindria contained a modified aspartate residue at position 71 (Minami et al, 1985).…”
Section: Introductionmentioning
confidence: 99%